Circulating metabolites and depression: a bidirectional Mendelian randomization - Dong, Yankai; Zou, Zengxiao; Deng, Pin; Fan, Xiaoping; Li, Chunlin (Frontiers in Neuroscience, 2023)
Background: Studies have shown an association between depression and circulating metabolites, but the causal relationship between them has not been elucidated. The purpose of this study was to determine whether there is a bidirectional causal relationship between circulating metabolites and depression, and to explore the role of circulating metabolites in reducing depression risk. Methods: In this study, the top SNPs associated with circular metabolite (n=24,925) and depression (n=322,580) were obtained from a publicly available genome-wide association study (GWAS) using a two-sample Mendelian randomization (MR) approach. SNPs estimates were summarized using inverse variance weighted meta-analysis, weighted median, MR Egger, MR Pleiotropy residuals and outliers (PRESSO) and “leave-one out” methods. Results: The Apolipoprotein A-1 (OR 0.9899, 95%CI 9806 to 0.9993) and glutamine (OR 0.9845, 95%CI 0.9718 to 0.9974) had protective causal effects on depression, while acetoacetate (OR 1.021, 95%CI 1.009 to 1.0343), glycoproteins (OR 1.005, 95%CI 1.0003 to 1.009), isoleucine (OR 1.013, 95%CI 1.002 to 1.024), urea (OR 1.012, 95%CI 0.996 to 1.028) had an anti-protective effect on depression. Reversed MR showed no effect of depression on the 7 circulating metabolites. Conclusions: MR Analysis in this study showed that Apolipoprotein A-1 and glutamine had a protective effect on depression, and acetoacetate, glycoprotein, isoleucine, glucose and urea may be risk factors for depression. Further research is needed to translate the findings into practice.